2016
DOI: 10.1111/pcn.12410
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cognitive impairment between schizophrenia and bipolar disorder: Considering the role of heterogeneity

Abstract: Schizophrenia is associated with significant cognitive impairment. Bipolar disorder (BD) also presents with cognitive deficits that are similar to, albeit less severe, than those reported in schizophrenia. There has been controversy over whether selective deficits in social cognition or developmental trajectory of cognitive deficits can distinguish schizophrenia from BD. Also, available studies have not generally considered the potential effect of cognitive heterogeneity within the two disorders on between-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 101 publications
(230 reference statements)
7
54
0
2
Order By: Relevance
“…It is also important to note that similar cross diagnostic differences between SCZ and BD have been reported by several previous studies that have examined neurocognition, functional magnetic resonance imaging (fMRI) and prevalence of metabolic syndrome . Studies have reported that patients with SCZ have greater impairment in cognitive functions compared to BD . A recent study has reported decreased volume of the CC (corpus callosum) associated with a lower degree of left hemispherical asymmetry for language in BD which was not replicated in SCZ.…”
Section: Discussionmentioning
confidence: 70%
“…It is also important to note that similar cross diagnostic differences between SCZ and BD have been reported by several previous studies that have examined neurocognition, functional magnetic resonance imaging (fMRI) and prevalence of metabolic syndrome . Studies have reported that patients with SCZ have greater impairment in cognitive functions compared to BD . A recent study has reported decreased volume of the CC (corpus callosum) associated with a lower degree of left hemispherical asymmetry for language in BD which was not replicated in SCZ.…”
Section: Discussionmentioning
confidence: 70%
“…The drug × gene × time interactions are significant, indicating cKO mice may bear different sensitivity to methylphenidate from control, although the key point is that there were increases overall, not decreases. We did not detect severe deficits in cognitive tests, and cognition is generally reported to be more severely altered in schizophrenia than bipolar disorder (27,47). Future studies could include more sensitive and sophisticated cognitive function tests.…”
Section: Discussionmentioning
confidence: 86%
“…Cognitive decline is one of the core features of patients with schizophrenia, and may be present, but is usually less prominent, in bipolar disorder (27). We performed Y maze tests (spatial learning and memory), and 1-h and 24-h novel object recognition tests (short-and long-term visual memory).…”
Section: Ank-g Cko Mouse Cortical Pyramidal Neurons Lose Ion Channel mentioning
confidence: 99%
“…Importantly, there may be substantial heterogeneity of premorbid intellectual functioning in BD, 62 as has been demonstrated in post-onset patients where some score lower on proxy measures of premorbid cognitive dysfunction and others do not. 5,63,64 A recent cross-diagnostic clustering study also indicated the presence of at least one subgroup comprising ~53% patients with BD and ~47% | 17 VAN RHEENEN Et Al. with SZ that demonstrated poor premorbid academic adjustment relative to controls.…”
Section: Summary and Insights Into Cognitive Trajectories From New mentioning
confidence: 99%